Penggunaan Media Visual Dalam Katekese Digital: Meningkatkan Daya Serap Informasi - Petriana Dae Lelangwayan; Emmeria Tarihoran (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The use of visual media in berkatekese can increase the effectiveness of learning in the digital era. In this day and age, digital technology has changed the way we learn and teach. This article discusses how visual media such as pictures, videos, animations can increase the absorption of information and the involvement of students in the learning process. Visual media not only enriches the learning experience but also helps teachers to convey material more easily and can be understood by students. In addition, the use of visual media in catechesis can help learning to be more effective in understanding the material and remembering students. The research method used in this article is a qualitative method with the main approach, namely direct observation at school and literature study. The results show that the use of visual media in learning can increase learner engagement and help in understanding learning materials well. Although it has shortcomings, it has benefits in supporting the learning process of Catholic religion in the digital era.